Pembatalan Sertipikat Hak Milik Dalam Jual Beli Tanah Sebagai Akibat Wanprestasi - Komang Edy Dharma Saputra (Universitas Mahendradatta, 2018)
Research with the theme of cancellation of freehold title in sale and purchase of land due to default aims to find out (1) How the procedure to cancel freehold title in sale and purchase of land due to default, and (2) How the legal consequence toward the cancellation of freehold title in sale and purchase of land due to default. This type of research used normative legal research which studying applicable laws and regulations in Indonesia. The source of legal materials were in the form of primary legal material, secondary legal material, and tertiary legal material and analysis was using hermeneutics analysis technique by interpreting legislation and studying more clearly the meaning contained in each article. The result of research shows that (1) the procedure to cancel freehold title in sale and purchase of land due to default is that the injured party may file a lawsuit in district court and PTUN (State Administrative Court), (2) legal consequence toward cancellation of freehold title in sale and purchase of land due to default is that the injured party has the rights to get legal protection and acquiring compensation from the default party.